SS-31 peptide enables mitochondrial targeting drug delivery: a promising therapeutic alteration to prevent hair cell damage from aminoglycosides - Xiao Kuang; Shuang Zhou; Weiling Guo; Zhenjie Wang; Yanhui Sun; Hongzhuo Liu (Taylor & Francis Group, 2017)
Aminoglycoside-induced hearing loss stems from damage or loss of mechanosensory hair cells in the inner ear. Intrinsic mitochondrial cell death pathway plays a key role in that cellular dysfunction for which no proven effective therapies against oto-toxicities exist. Therefore, the aim of the present study was to develop a new mitochondrial targeting drug delivery system (DDS) that provided improved protection from gentamicin. Particularly, SS-31 peptide-conjugated geranylgeranylacetone (GGA) loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles were constructed successfully via emulsion-solvent evaporation method. The zebrafish lateral line sensory system was used as an in vivo evaluating platform to investigate the protective efficiency against gentamicin. SS-31 modification significantly reduced the activity of mechanoelectrical transduction (MET) channel and gentamicin uptake in zebrafish lateral line hair cells. As expected, SS-31 conjugated nanoparticles showed mitochondrial specific accumulation in hair cells when compared with unconjugated formulations. Furthermore, intracellular SS-31 modified PLGA NPs slightly enhanced mitochondrial membrane potential (MMP, ΔΨm) and then returned to a steady-state, indicating their effect on the respiratory chain complexes in mitochondria. GGA loaded SS-31 conjugated nanoparticles demonstrated the most favorable hair cells survivals against gentamicin when compared with unconjugated groups whereas blank formulations failed to exhibit potency, indicating that the efficiency was attributed to drug delivery of GGA. These results suggest that our constructed mitochondria-targeting PLGA based DDS have potential application in protecting hair cells from ototoxic agents.